Camrelizumab (SHR-1210) alone or in combination with gemcitabine plus cisplatin for nasopharyngeal carcinoma: results from two single-arm, phase 1 trials. Issue 10 (October 2018) - Fang, Wenfeng; Yang, Yunpeng; Ma, Yuxiang; Hong, Shaodong; Lin, Lizhu; He, Xiaohui; Xiong, Jianping; Li, Ping; Zhao, Hongyun; Huang, Yan; Zhang, Yang; Chen, Likun; et al.
Summary: Background: Platinum-based doublet chemotherapy regimens, preferentially gemcitabine plus cisplatin, are generally considered the first-line standard of care for patients with recurrent or metastatic nasopharyngeal carcinoma. However, no consensus has been reached regarding treatment following progression after first-line therapy. Camrelizumab (SHR-1210) is a humanised anti-programmed death-1 (anti PD-1) antibody. We present safety and preliminary antitumour activity of camrelizumab alone as second-line therapy in patients with recurrent or metastatic nasopharyngeal carcinoma and combined with gemcitabine and cisplatin as first-line therapy in this patient population. Methods: We report the results from two single-arm, phase 1 trials. Both trials included patients aged 18–70 years with histologically or cytologically confirmed nasopharyngeal carcinoma and confirmed metastatic disease or locoreginal recurrence, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients who received at least one previous line of treatment were enrolled at five academic hospitals in China into the dose-escalation and expansion trial to receive camrelizumab monotherapy intravenously at escalating doses of 1 mg/kg, 3 mg/kg, and 10 mg/kg, and a bridging dose of 200 mg per dose once every 2 weeks (monotherapy trial). Treatment-naive patients were enrolled from a single centre in China to receive six cycles of camrelizumab 200 mg (day 1), gemcitabine 1 g/m 2 (days 1 and 8), and cisplatin 80 mg/m 2 (day 1) every 3 weeks followed by camrelizumab 200 mg maintenance once every 3 weeks (combination trial). The primary endpoint of both trials was the safety and tolerability of the study treatment. Analyses were done per protocol. Both trials are registered withClinicalTrials.gov, numberNCT02721589 (camrelizumab monotherapy trial) andNCT03121716 (camrelizumab combination trial). Both trials are ongoing, but are no longer enrolling patients. Findings: In the camrelizumab monotherapy trial, between March 31, 2016, and Sept 20, 2017, 121 patients were assessed for eligibility, of whom 93 patients were enrolled across the dose-escalation and expansion cohorts and received at least one dose of camrelizumab (safety population). 15 (16%) of 93 patients had treatment-related adverse events of grade 3 or 4, the most common of which were elevated conjugated bilirubin concentration (three [3%] of 93 patients), stomatitis, anaemia, and increased concentrations of aspartate aminotransferase, alanine aminotransferase, and total bilirubin, each of which occurred in two (2%) patients. Eight (9%) patients had a treatment-related serious adverse event. No dose-limiting toxic effects were observed during the dose-escalation phase. 31 (34%; 95% CI 24–44) of 91 evaluable patients on camrelizumab monotherapy had an overall response with a median follow-up of 9·9 months (IQR 8·1–11·7). In the camrelizumab combination trial, between April 18, 2017, and Aug 15, 2017, 24 patients were assessed for eligibility, of whom 23 patients were enrolled and treated (safety population). 20 (87%) of 23 patients had grade 3 or 4 treatment-related adverse events: neutropenia (13 [57%] of 23 patients), anaemia (11 [48%] patients), leucopenia (11 [48%] patients), thrombocytopenia (seven [30%] patients), oedema (two [9%] patients), hyponatraemia (two [9%] patients), hypochloraemia (one [4%] patients), and rash (one [4%] patient). Two patients had treatment-related serious adverse events. No treatment-related deaths occurred in these trials. 20 (91% [95% CI 72–97]) of 22 evaluable patients had an overall response with a median follow-up time of 10·2 months (IQR 9·7–10·8). Interpretation: Camrelizumab is a well tolerated, potential treatment option for patients with recurrent or metastatic nasopharyngeal carcinoma. The combination of camrelizumab plus gemcitabine and cisplatin has a manageable toxicity profile and promising preliminary antitumour activity for this disease in treatment-naive patients. Randomised controlled trials are needed to further establish the role of immune checkpoint inhibition for nasopharyngeal carcinomas. Funding: Hengrui Medicine Co, Chinese National Natural Science Foundation project, Science and Technology Program of Guangdong, Pearl River Nova Program of Guangzhou.